Enhanced efficiency in CO2-free hydrogen production from methane in a molten liquid alloy bubble column reactor with zirconia beads - Noh, Yong Gyu; Lee, Young Jae; Kim, Jina; Kim, Yu Kwon; Ha, Jung Seub; Kalanur, Shankara S.; Seo, Hyungtak (Chemical Engineering Journal, 2021)
The CO2-free production of hydrogen is an important criterion for the development of future hydrogen economy along with environmental protection. In this work, a new and efficient strategy for catalytic methane pyrolysis to hydrogen production was proposed using a multi-stage bubble column reactor containing molten Ni-Bi alloy, zirconia and molten NaBr. Compared to the 2-stage bubble column reactor, the 3-stage bubble column reactor was found to enhance the methane conversion rate from 32% to 37% at 985 °C. The analysis of the carbon products revealed that similar kinds of amorphous and graphitic carbon-based materials can be obtained from both reactors. The enhanced methane pyrolysis rates with the use of zirconia beads indicate that they can be employed to control the bubble behavior and to enhance the contact area between bubbles and the liquid catalyst surface for an efficient bubble column reactor with liquid metal alloy catalysts.
Keywords: Bubble column reactors; Carbon production; Enhanced efficiency; Hydrogen economy; Hydrogen generations; Liquid alloy; Methane pyrolysis; Molten liquids; Production of hydrogen; Zirconium bead; Bubble column reactor; Carbon production; Hydrogen generation; Methane pyrolysis; Zirconia beads